(untitled) (Medico Legal Update, 2020)
Preeclampsia (PE) is characterized by endothelial dysfunction with vasoconstriction due to cell adhesion molecules or mediators released by defective placentation. Platelet selectin (P-selectin) and epithelial cadherin (E-cadherin) are the cell adhesion molecules, is elevated in many inflammatory conditions including PE. Objective: To investigate if P-selectin and E-cadherin levels can be used as a marker for adverse outcomes in pregnancy complicated with PE. Patients and Method: This study involved 90 pregnant women in their third trimester of pregnancy divided into2 group: Group A: involves 45 pregnant women with PE. Group B: involve 45 healthy pregnant women and normal fetal growth (Control group). Result: The results show there were a high significant increase in the mean values of P-selectin with high increase in the mean values of E-cadherin in PE group when compared to control group. ROC curve shows sensitivity and specificity and false positive rate for predication of PE by P-selectin and E-cadherin in control and patients groups, and the maximum accuracy for the P-selectin and E-cadherin in discrimination between control and PE patients groups. Conclusions: There is an inverse relationship between cell adhesion molecules and selenium in PE compared with normal pregnancy. High level of serum P-selectin and E-cadherin are associated with the presence PE, which provide additional information for predicting of PE and preventing its complications and for better understanding pathogenesis of PE